Molecular Cloning and Sequencing of AlkalophilicCellulosimicrobium cellulans CKMX1 Xylanase Gene Isolated from Mushroom Compost and Characterization of the Gene Product - Walia,Abhishek (2015)
ABSTRACT A xylanolytic bacterium was isolated from mushroom compost by using enrichment technique. Results from the metabolic fingerprinting, whole-cell fatty acids methyl ester analysis and 16S rDNA sequencing suggested the bacterium to be Cellulosimicrobium cellulans CKMX1. Due to the xylanolytic activity of this bacterium, isolation and characterization of the xylanase gene were attempted. A distinct fragment of about 1671 bp was successfully amplified using PCR and cloned into Escherichia coli DH5α. A BLAST search confirmed that the DNA sequence from the amplified fragment was endo-1, 4-beta-xylanase, which was a member of glycoside hydrolase family 11. It showed 98% homology withCellulosimicrobium sp. xylanase gene (Accession no. FJ859907.1) reported from the gut of Eisenia fetida in Korea. In silicophysico-chemical characterization of amino acid sequence of xylanase showed an open reading frame encoding a 556 amino acid sequence with a molecular weight of 58 kDa and theoretical isolectric point (pI) of 4.46 was computed using Expasy's ProtParam server. Secondary and homology based 3D structure of xylanase was analysed using SOPMA and Swiss-Prot software.